Analysis of mode characteristics for microcircular resonators confined by different metallic materials - 姚齐峰 黄永箴 杨跃德 肖金龙 (Journal of semiconductors, 2016)
Mode characteristics of metallically confined microcircular resonators are theoretically studied by solv- ing eigenvalue equations for two-dimensional multilayer structures. The influences of conventional metals includ- ing Au, Ag, Cu, A1, and Ti, on the mode wavelengths and Q factors of whispering gallery modes （WGMs） are an- alyzed and compared. The results show silver has the best optical confinement among these metals, and aluminum presents similar behavior to Au. However, Ti, which is usually applied to enhance the adhesion of p-electrode to semiconductors, results in a great dissipation for confined modes. Furthermore, circular microlasers with A1 as both p-electrode and optical confinement medium are fabricated, and continuous-wave operations are realized at room temperature for the microlasers with a radius of 15μm.